2017
DOI: 10.3349/ymj.2017.58.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Pretreatment Improves Cognition and Reduces Hippocampal Damage Via p38 Mitogen-Activated Protein Kinase in a Rat Model

Abstract: PurposeTo investigate the effects of hyperbaric oxygen (HBO) pretreatment on cognitive decline and neuronal damage in an Alzheimer’s disease (AD) rat model.Materials and MethodsRats were divided into three groups: normal saline (NS), AD, and HBO+AD. In the AD group, amyloid β peptide (Aβ)1-40 was injected into the hippocampal CA1 region of the brain. NS rats received NS injection. In the HBO+AD group, rats received 5 days of daily HBO therapy following Aβ1-40 injection. Learning and memory capabilities were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…In a mouse model of AD, Shapira et al found that HBO therapy can improve cognitive function by reducing neuroinflammation 23 . In a rat model of AD, Zhao et al showed that HBO therapy can reduce hippocampal neuronal apoptosis and thus improve cognitive function by reducing phosphorylation of the P38 MAPK signaling pathway 24 . In addition to AD, HBO therapy can also improve cognitive function in VD.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of AD, Shapira et al found that HBO therapy can improve cognitive function by reducing neuroinflammation 23 . In a rat model of AD, Zhao et al showed that HBO therapy can reduce hippocampal neuronal apoptosis and thus improve cognitive function by reducing phosphorylation of the P38 MAPK signaling pathway 24 . In addition to AD, HBO therapy can also improve cognitive function in VD.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent studies, we have demonstrated that thrombin stimulates MAPK activation via PKCs and PI3K/Akt-dependent cascades, resulting in MMP-9 expression and cell migration in SK-N-SH cells [20,21]. Moreover, MAPKs have also been known to possess an important role in the regulation of the pathological processes of several CNS inflammatory disorders, such as stroke and AD [58,59,60,61]. Furthermore, several reports have shown that galangin elicits anti-inflammatory effects by inhibiting MAPK phosphorylation [62,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that HBOT can ameliorate Alzheimer disease pathology and behavioural deficits in a transgenic mouse model of Alzheimer disease. Furthermore, in another rodent model of Alzheimer disease, Zhao et al (2017) proved that HBOT can reduce hippocampal neuronal (Sarno et al, 1972b) 16 left hemisphere stroke patients 1 session of HBO for 90 min at 2 ATA Token Test, Functional Communication Profile No improvement (Sarno et al, 1972a) (Kalaria et al, 2008). Vascular dementia is group of syndromes based on varying vascular mechanisms, such as multiple infarcts, small vessel ischaemic disease, strategically placed infarcts, hypoperfusion and haemorrhage, Alzheimer disease with cerebrovascular disease, hereditary vascular dementia or cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (Brien et al, 2003).…”
Section: Hbot Usage For Cognitive Ageing and Neurodegenerative Disordersmentioning
confidence: 99%